A robust low cost device for measuring road induced vibrations - Mason, G.; Larson, M.; Deng, R.; Reed, D.; Pahlmeyer, M.; Wright, N.; Wu, Z. P.; Yahata, J. (Journal of Science and Cycling, 2016)
Road induced vibrations have been linked to cycling comfort and fatigue. Currently, vibration tests are preformed using expensive equipment which is often unsuitable for tests involving large numbers of cyclists riding in real-world conditions in inclement weather. A robust low-cost device was developed to address this shortcoming. The device is capable of measuring vibrations at both axles for extended periods of time. Data collected includes vibrational information, GPS coordinates and time. The system uses custom hardware base on readily available components, costing approximately $100 US, and a smartphone. It weighs 130 g plus the weight of the smartphone and can collect data for over 12 hours on a single charge. The syste was validated using controlled tests with a single rider on a closed course, and on commuter bicycles in an urban setting.